Carboplatin and hypomagnesemia: Is it really a problem?. Issue 6 (13th October 2020) - Gaughran, Gregory; Qayyum, Kiran; Smyth, Lillian; Davis, Alison
Abstract: Background: Carboplatin has largely replaced cisplatin in ovarian/peritoneal/tubal cancer (OC) due to comparable activity and reduced toxicity, particularly nephrotoxicity and hypomagnesemia. Anecdotally hypomagnesemia occurs commonly with carboplatin, however there are limited data available regarding frequency or severity. Aims: To quantify incidence and severity of hypomagnesemia in patients receiving carboplatin‐based chemotherapy for OC; to explore a dose‐response relationship with carboplatin and assess potential confounding variables. Methods: A retrospective single‐center review of all OC patients receiving carboplatin‐based chemotherapy as first/subsequent line between 2012 and 2018 was performed. Data on patient/disease characteristics, potential confounders (gastrointestinal/renal impairment, premorbid hypomagnesemia and concomitant medications), dose, electrolytes, and magnesium replacement were collected. Results: One hundred four of 144 (72%) patients had at least one hypomagnesemia event, 11 of 104 (11%) grade 2, and 11 of 104 (11%) grade 3/4 in severity. Multivariate analysis showed a significant association between hypomagnesemia and treatment duration ( P  < .001). Premorbid hypomagnesemia was associated with a significantly longer duration and higher grade of hypomagnesemia ( P  = .021 and P  < .001, respectively). Vomiting, diarrhea, and confounding medications were associated with hypomagnesemia ( P  = .019 and P  = .028, respectively). Fourteen percent of hypomagnesemia events never resolved suggesting a significant cohort post‐carboplatin are at risk of long‐term renal toxicity. The effect of magnesium replacement could not be accurately assessed due to limited documentation of replacement. Conclusion: Hypomagnesemia is common in patients receiving carboplatin‐based chemotherapy for OC, and although generally mild, a significant minority were severe. Several high‐risk groups were identified including patients with premorbid hypomagnesemia, vomiting, diarrhea, or taking certain medications. Further research is warranted to understand when hypomagnesemia is clinically relevant and determine the impact of interventions.